2017
DOI: 10.2147/ott.s137000
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment combination of platelet counts and neutrophil–lymphocyte ratio predicts survival of nasopharyngeal cancer patients receiving intensity-modulated radiotherapy

Abstract: BackgroundIncreased cancer-related inflammation has been associated with unfavorable clinical outcomes. The combination of platelet count and neutrophil–lymphocyte ratio (COP-NLR) has related outcomes in several cancers, except for nasopharyngeal carcinoma (NPC). This study evaluated the prognostic value of COP-NLR in predicting outcome in NPC patients treated with intensity-modulated radiotherapy (IMRT).Materials and methodsWe analyzed the data collected from 232 NPC patients. Pretreatment total platelet coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 38 publications
(68 reference statements)
1
36
0
1
Order By: Relevance
“…Lu A et al [ 36 ] revealed that NLR ≥ 2.28 indicated poor OS and PFS, with PLR ≥ 174 correlated with inferior OS. Lin et al [ 37 ] believed the combination of platelet with NLR (COP-NLR score) was a better predictor compared with NLR alone or APC alone. A latest meta-analysis by Su et al [ 38 ] evaluated the hematological parameters in NPC patients, and suggested the significant role of NLR and lymphocyte in prognostic prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Lu A et al [ 36 ] revealed that NLR ≥ 2.28 indicated poor OS and PFS, with PLR ≥ 174 correlated with inferior OS. Lin et al [ 37 ] believed the combination of platelet with NLR (COP-NLR score) was a better predictor compared with NLR alone or APC alone. A latest meta-analysis by Su et al [ 38 ] evaluated the hematological parameters in NPC patients, and suggested the significant role of NLR and lymphocyte in prognostic prediction.…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, high pretreatment PLR and NLR promote tumor spread, tumor cell invasion, and adhesion 10 . In addition, many studies have established the prognostication value of a new cancer-related inflammatory system, that is, the combination of inflammation indices on many malignant tumors, such as non-small cell lung cancer, gastric cancer, and nasopharyngeal cancer 11 - 13 . We developed a novel inflammation-based score system to predict survival outcomes using five preoperational inflammatory markers in HCC after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Although the adjuvant chemotherapy of colorectal cancer have greatly improved several decades, survival outcomes still remain a poor prognosis and leads most common cause of cancer-related death. 14 CoNLR-PLR, combined neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio.…”
Section: Discussionmentioning
confidence: 99%